IDENTIFIKASI KEPUASAN BELAJAR DI ERA PENDIDIKAN 4.0 - Khakim Alfarizi, Abdul; Sugiarti, Rini; Erlangga, Erwin (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
The objective to be achieved in this study is to identify learning satisfaction at SMP X Salatiga. This type of research is qualitative research and uses a case study method. Data sources in this study include primary sources, namely the results of observations and interviews of two individual junior high school students and secondary sources in the form of field documentation and social media. Data collection was carried out using observation, interviews, and documentation. Data analysis techniques were carried out using data reduction, data presentation, and drawing conclusions. Checking the validity of the data using observation diligence and giving check. The results of the study showed that from the five it can be concluded that student learning satisfaction at SMP X varies greatly. Some students are satisfied with the reliability, responsiveness, certainty, empathy, and physical evidence provided by the school, while other students stated that there were shortcomings in these aspects that reduced their satisfaction in the learning process.